Effects of extending disadvantaged families' teaching of emergent literacy. Issue 3 (3rd May 2020) - Hannon, Peter; Nutbrown, Cathy; Morgan, Anne
ABSTRACT: Intervention to raise the literacy achievement of disadvantaged groups in society has focused on preschool literacy development because it is predictive of later educational achievement and because research has shown that key strands of literacy emerge very early in childhood. Intervention programmes to promote emergent literacy are likely to be more effective if they involve families rather than children alone but meta-analyses reveal effect sizes for family-based programmes are variable and generally lower for disadvantaged families. This article suggests reasons for limited effectiveness and reports a study of a preschool intervention programme that used a particular conceptual framework, and approach, in working with families to extend their facilitative (rather than instructional) teaching of several strands of emergent literacy. Disadvantaged families with three-year-olds were invited to join a long-duration, low-intensity programme before school entry. Home visiting was a core component of the programme, alongside community based and centre-based activities, supplemented by other means of communication. A randomised controlled trial, involving 176 families, was used to investigate effects on children's literacy at the end of the programme and two years later. The intervention was found to be effective; effects persisted at follow up for children of mothers with low educational levels. Practice, policy and future research implications are discussed.